2017
DOI: 10.3354/aei00232
|View full text |Cite
|
Sign up to set email alerts
|

Maternal inheritance influences homing and growth of hybrid offspring between wild and farmed Atlantic salmon

Abstract: The occurrence of domesticated organisms in nature is a major biological issue. Many can survive and reproduce with wild conspecifics, but little is known about the ecology of the hybrid offspring. Here, we investigated recapture, homing and growth of the released offspring of farmed (domesticated) and wild Atlantic salmon Salmo salar as well as their crosses. The fish were hatchery-reared for 1 yr and released as smolts in the River Imsa, Norway, the home river of the wild fish. The released fish migrated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 58 publications
(36 reference statements)
6
17
2
Order By: Relevance
“…Based upon results from these simulations, together with existing knowledge, we suggest that a combination of reduced spawning success of domesticated escapees, natural selection purging maladapted phenotypes/genotypes from the wild population, and phenotypic plasticity buffer the rate and magnitude of change in phenotypic and demographic characteristics of wild populations subject to spawning intrusion of domesticated escapees. These suggestions are in line with empirical data demonstrating that domesticated escapees display reduced spawning success in comparison with wild salmon (Fleming et al., , ), the offspring of domesticated salmon display reduced survival in the wild when compared to wild fish (Fleming et al., ; McGinnity et al., , ; Skaala et al., ) and that differences between domesticated and wild salmon in phenotypic traits, such as growth rate, are much less pronounced in the wild than in the hatchery (Besnier et al., ; Jonsson & Jonsson, ; Reed et al., ; Skaala et al., ).…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Based upon results from these simulations, together with existing knowledge, we suggest that a combination of reduced spawning success of domesticated escapees, natural selection purging maladapted phenotypes/genotypes from the wild population, and phenotypic plasticity buffer the rate and magnitude of change in phenotypic and demographic characteristics of wild populations subject to spawning intrusion of domesticated escapees. These suggestions are in line with empirical data demonstrating that domesticated escapees display reduced spawning success in comparison with wild salmon (Fleming et al., , ), the offspring of domesticated salmon display reduced survival in the wild when compared to wild fish (Fleming et al., ; McGinnity et al., , ; Skaala et al., ) and that differences between domesticated and wild salmon in phenotypic traits, such as growth rate, are much less pronounced in the wild than in the hatchery (Besnier et al., ; Jonsson & Jonsson, ; Reed et al., ; Skaala et al., ).…”
Section: Discussionsupporting
confidence: 70%
“…Within regions displaying a mosaic of small and large populations, straying and the degree of genetic connectivity may be skewed, whereby large populations can act as net‐exporters of strayers to smaller neighboring wild populations (Hansen, Skaala, Jensen, Bekkevold, & Mensberg, ). Straying of wild fish between rivers (Stabell, ) also varies in time and space for Atlantic salmon (Jonsson & Jonsson, ; Jonsson et al., ; Pedersen et al., ; Skilbrei & Holm, ) and other salmonids (Bett, Hinch, Burnett, Donaldson, & Naman, ; Ford, Murdoch, & Hughes, ; King, Hillman, Elsmere, Stockley, & Stevens, ). Recent experimental work has also indicated that introgression of domesticated salmon may increase straying rates in impacted wild Atlantic salmon populations (Jonsson & Jonsson, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations